2010
DOI: 10.1128/jcm.02055-09
|View full text |Cite
|
Sign up to set email alerts
|

Rubella Virus Genotypes in the People's Republic of China between 1979 and 2007: a Shift in Endemic Viruses during the 2001 Rubella Epidemic

Abstract: The incidence of rubella cases in China from 1991 to 2007 was reviewed, and the nucleotide sequences from 123 rubella viruses collected during 1999 to 2007 and 4 viral sequences previously reported from 1979 to 1984 were phylogenetically analyzed. Rubella vaccination was not included in national immunization programs in China before 2007. Changes in endemic viruses were compared with incidences of rubella epidemics. The results showed that rubella epidemics occur approximately every 6 to 8 years (1993/1994, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
39
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 24 publications
1
39
0
1
Order By: Relevance
“…Of the cases for whom vaccination history was available, 10% had received one dose of MMR vaccine and none had received two doses. Since the year 2000, rubella outbreaks have occurred among undervaccinated populations in several countries, including Brazil, 66 China, 67 India 68 and Spain. …”
Section: Acknowledgementsmentioning
confidence: 99%
“…Of the cases for whom vaccination history was available, 10% had received one dose of MMR vaccine and none had received two doses. Since the year 2000, rubella outbreaks have occurred among undervaccinated populations in several countries, including Brazil, 66 China, 67 India 68 and Spain. …”
Section: Acknowledgementsmentioning
confidence: 99%
“…Whole genome sequences of four genotype 1E and seven genotype 2B viruses were previously determined611. In China, the previously endemic RV genotypes were likely 2A and 1F (before 2002) but both were replaced by genotype 1E12. Although genotype 1E is currently detected most frequently, an increasing number of genotype 2B viruses are now detected.…”
mentioning
confidence: 99%
“…Although genotype 1E is currently detected most frequently, an increasing number of genotype 2B viruses are now detected. Some of the genotype 2B viruses are believed to be imported, while others are likely due to endemic transmission121314. Analysis based on 739-nt sequences, showed that viruses of genotype 1E from China were genetically distinct from viruses collected elsewhere and could be divided into two distinct clusters, Cluster A (1E-A) and Cluster B (1E-B)13.…”
mentioning
confidence: 99%
“…The results of molecular epidemiology studies of rubella viruses in China indicate that 5 (1a, 1E, 1F, 2A, and 2B) out of the 13 genotypes have been present in China since 1979, and cocirculation of these different genotypes has been observed (34). Before the introduction of the rubella vaccine into the national immunization program in 2008, rubella epidemics were common.…”
mentioning
confidence: 99%
“…According to the rubella surveillance data, rubella epidemics occurred approximately every 6 to 8 years in China. A shift in the predominant genotype from 1F and 2B to 1E coincided with the 2001 rubella epidemic, and 1E subsequently became the most common genotype (34).…”
mentioning
confidence: 99%